Netter's concise neuroanatomy - Rubin, Michael, 1957- 4 0 16; (Frank Henry), 1906-1991. Safdieh, Joseph E.;Netter, Frank H.; 5 (Philadelphia, PA : Saunders Elsevier, 2007)
An overview of the various aspects of neuroanatomy, with illustrations and tables that demonstrate the components of nervous system anatomy and the functional importance and clinical significance of each anatomical structure.
Bony coverings of the brain and spinal cord -- Gross anatomy of the brain and spinal cord -- Blood vessels of the brain and spinal cord -- Cerebrospinal fluid and coverings of the brain -- Medulla oblongata -- Pons -- Midbrain (mesencephalon) -- Thalamus -- Basal ganglia -- Cerebellum -- Cerebral cortex -- Hypothalamus -- Limbic system -- Cranial nerves I-XII -- Major sensory and motor pathways -- Reticular formation -- Anatomy of the peripheral nervous system: upper extremity -- Anatomy of the peripheral nervous system: lower extremity -- Autonomic nervous system.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; anatomy & histology -- Neuroanatomy;Nervous System;Nervous System Diseases;Neuroanatomy;Anatomy -- Atlases.;Atlases.;Atlases.;Atlases.;Atlases.; 20; 2